Hydrogel-Based Scaffolds in Oral Tissue Engineering - Ayala-Ham, Alfredo; López-Gutierrez, Jorge; Bermúdez, Mercedes; Aguilar-Medina, Maribel; Sarmiento-Sánchez, Juan Ignacio; López-Camarillo, César; Sanchez-Schmitz, Guzman; Ramos-Payan, Rosalio (Frontiers in Materials, 2021)
Regenerative therapy in dentistry has gained interest given the complexity to restore dental and periodontal tissues with inert materials. The best approach for regeneration requires three elements for restoring functions of affected or diseased organ tissues: cells, bioactive molecules, and scaffolds. This triad is capable of modulating the processes to replace lost or damaged tissues and restore function, as it has an impact on diverse cellular processes, influencing cell behavior positively to induce the complete restoration of function and morphology of such complex tissues. Hydrogels (HG) have shown advantages as scaffolds as they are soft and elastic three-dimensional (3D) networks formed from hydrophilic homopolymers, copolymers, or macromers. Besides simple or hybrid, HG show chemical, mechanical and biological activities such as the incorporation of cells in their structures, the retention of high-water content which enhances the transportation of cell nutrients and waste, and elastic and flexible characteristics that emulate the native extracellular matrix (ECM). HG can induce changes in cellular processes such as chemotaxis, proliferation, angiogenesis, biomineralization and expression of specific-tissue biomarkers, enhancing regeneration process. Besides some of them have anti-inflammatory and anti-bacterial effect. This review aims to compile the most relevant information regarding advances in HG for dental and periodontal tissue regeneration, their biological effects, and their clinical implications. Even though most of the HG are still under investigation, some of them have been studied in vitro and in vivo with outstanding results that may lead to preclinical studies. Besides there are HG that have shown their efficacy in patients such as 0.2 and 0.8% hyaluronan HG that enhances the healing of gingival tissue.